Localization of aquaporins in the mouse vestibular end organs. (August 2013) - Takumida, Masaya; Takumida, Hiroshi; Kakigi, Akinobu; Egami, Naoya; Nishioka, Rie; Anniko, Matti
Abstract Conclusion: We found that aquaporins (AQPs) in the fluid transporting cells, such as vestibular dark cells and endolymphatic sac epithelial cells, seem to be of importance in fluid transport in the inner ear, while those in the sensory and ganglion cells may play a functional role in sensory cell transduction. Objective: Expression of AQPs (0–12) was analyzed in normal mouse vestibular end organs. Methods: CBA/J mice were used in this study. Localization of AQPs 0–12 in the vestibular end organs and endolymphatic sac was investigated by immunohistochemistry. Results: The AQPs were found abundantly distributed in many structures in the vestibular end organs, i.e. vestibular sensory and supporting cells, vestibular dark cells, vestibular ganglion cells, and the endolymphatic sac.